ARBITRAL AGREEMENT - Пицхелаурі, Ніколоз (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The work thoroughly presents the characteristics and analysis of the Georgian law of arbitration. Theimproved arbitral legislation is directly connected to the foreign investing. When having the businessrelations to the Georgian party they need the stable legislative base and first of all the alternative analysis ofsolving disputes suitable to the international level standards. The society’ interest and the court supporttoward the arbitral law is also important.